A comparative study of al-Ghazali’s and Ibn Taymiyyah’s views on sufism - Arikewuyo, Ahmed Nafiu (Penerbit Universiti Kebangsaan Malaysia, 2020)
Sufism has generated from the ancient time a very staunch polemics among Muslim scholars. The controversy over sufism has attracted various comments and remarks over the unique and peculiar tenets of sufis. Among the Muslim scholars who have contributed to the discourse were al-Ghazali and Ibn Taymiyyah. This research aims to compare the views of these two scholars. Library research with analytic and comparative methodology was adopted. Findings show that both scholars are credited to have reformed some popular and conventional doctrines of the Sufis of their respective times. In addition, al-Ghazali and Ibn Taymiyyah agreed that some innovations and perversions have found their way into sufism. A major phenomenon in the views of the two scholars on sufism is that while al-Ghazali was to a very large extent influenced by some sufi superstitions, Ibn Taymiyyah strongly subjects sufism to the literal provisions of the Quran and Sunnah. It is the conclusion of this paper that while it is accurate to ascribe al-Ghazali to sufism, it is inaccurate to regard Ibn Taymiyyah as one despite some of his sympathetic views on some sufis.